2019
DOI: 10.3390/ijerph16162810
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Emotional Intelligence, Motivation and Resilience on Academic Performance and the Adoption of Healthy Lifestyle Habits among Adolescents

Abstract: Included among the basic objectives of Physical Education (PE) classes is the consolidation of habits of a healthy lifestyle among adolescents. However, the main studies in this field have focused on cognitive aspects related to students during these classes, yet they ignore the role that emotions can play in the adoption of future habits. Objectives: To analyze how emotions (emotional intelligence and emotional state) can influence the resilience and motivation of adolescents, as well as academic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 55 publications
7
80
2
5
Order By: Relevance
“…This situation causes a change in the habits of young people related to the practice of physical activity and food, which can produce a decrease and even abandonment of those behaviors related to healthy habits. However, there are a series of internal mechanisms related to adaptive habits that are essential to overcome the possible vicissitudes that may occur, such as the recognition of emotions and resilience [3][4][5]. Therefore, this study aims to analyze…”
Section: Introductionmentioning
confidence: 99%
“…This situation causes a change in the habits of young people related to the practice of physical activity and food, which can produce a decrease and even abandonment of those behaviors related to healthy habits. However, there are a series of internal mechanisms related to adaptive habits that are essential to overcome the possible vicissitudes that may occur, such as the recognition of emotions and resilience [3][4][5]. Therefore, this study aims to analyze…”
Section: Introductionmentioning
confidence: 99%
“…When students are intrinsically motivated, they tend to be active and participative due to the enjoyment and internal satisfaction derived from the physical, psychological and emotional sensations of the activities carried out in class [3,4]. On the other hand, more controlling forms of motivation are bad predictors of long-term adherence [5], such as participating in class to alleviate negative feelings (e.g., anxiety, shame) or to avoid something negative (e.g., grades, punishments). Mindfulness is a factor that can distinguish those students who are intrinsically motivated from those who are extrinsically motivated because it determines the degree to which students who are mentally involved in the class instead of paying attention to external distractors, irrelevant thoughts or anticipated outcomes while performing different activities [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a study by Araya and Jimenez, [55] in the area of PE classes showed how high levels of creativity positively predicted positive emotions and negatively predicted negative ones. On the other hand, a study by Ivcevic, Brackett, and Mayer [56] showed that creativity correlated positively with emotional intelligence, the latter being a precursor of positive moods and a protector against negative emotions [57]. These results can be explained by the fact that PE students with higher levels of creativity allow students to solve motor problems more quickly and effectively, thus experiencing fun and joy, positive emotions.…”
Section: Discussionmentioning
confidence: 99%